2018
DOI: 10.1557/adv.2018.278
|View full text |Cite
|
Sign up to set email alerts
|

Human Stem Cell Derived Osteocytes in Bone-on-Chip

Abstract: Human mesenchymal stem cells were reseeded in decellularized human bone subject to a controlled mechanical loading to create a bone-on-chip that was cultured for over 26 months. The cell morphology and their secretome were characterized using immunohistochemistry and in situ immunofluorescence under confocal microscopy. The presence of stem cell derived osteocytes was confirmed at 547 days. Different cell populations were identified. Some cells were connected by long processes and formed a network. Comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Similarly, in bone‐on‐chip studies, relatively soft hydrogels are a poor mimic of native bone matrix. Therefore, different biomaterials have been used to mimic the hard, mineralized ECM of bone, including fibrin incorporating hydroxyapatite, [ 237 ] mineralized collagen, [ 227 ] and tightly packed calcium phosphate microbeads, [ 194 ] as well as decellularized human [ 238 ] or animal [ 239 ] bone. These models have been used to investigate cancer metastasis into bone [ 227,239 ] or bone angiogenesis, [ 193 ] to investigate the mechanotransduction of osteocytes, [ 194 ] and to study the effect of mechanical stimulation on bone formation over timescales of multiple years.…”
Section: Biomaterials As Tools For On‐chip Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in bone‐on‐chip studies, relatively soft hydrogels are a poor mimic of native bone matrix. Therefore, different biomaterials have been used to mimic the hard, mineralized ECM of bone, including fibrin incorporating hydroxyapatite, [ 237 ] mineralized collagen, [ 227 ] and tightly packed calcium phosphate microbeads, [ 194 ] as well as decellularized human [ 238 ] or animal [ 239 ] bone. These models have been used to investigate cancer metastasis into bone [ 227,239 ] or bone angiogenesis, [ 193 ] to investigate the mechanotransduction of osteocytes, [ 194 ] and to study the effect of mechanical stimulation on bone formation over timescales of multiple years.…”
Section: Biomaterials As Tools For On‐chip Biologymentioning
confidence: 99%
“…These models have been used to investigate cancer metastasis into bone [ 227,239 ] or bone angiogenesis, [ 193 ] to investigate the mechanotransduction of osteocytes, [ 194 ] and to study the effect of mechanical stimulation on bone formation over timescales of multiple years. [ 238 ]…”
Section: Biomaterials As Tools For On‐chip Biologymentioning
confidence: 99%
“…These systems displayed multi-level spatial reorganisation of the cells, and the collagen fibres. 29 Hence, this bone-on-chip system makes it possible to simultaneously study the effects of mechanical stimulations and age on bone cell differentiation, their calcium mechanobiology and the quality of the bone they form over very long periods of time (at least over two years).…”
Section: Studying Human Bone Formation In a Bone-on-chipmentioning
confidence: 99%
“…In recent years, multiple 3D in vitro cell culture models for bone have been developed to study variable aspects of bone development 7, 8 9 10 , which significantly improved the physiological relevance of bone cell cultures compared to previously used monolayer systems. These studies showed that mechanical stimulation 9,10 and matrix stiffness 7 are critical influencers of bone formation with regard to differentiation and bone matrix maturation. Remarkably, some of these 3D models showed that inducing longitudinal strain by fixation of a 3D cell culture on opposite sides was enough to induce matrix alignment and aligned mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multiple 3D in vitro cell culture models for bone have been developed to study variable aspects of bone development (Akiva et al, 2021; Budyn et al, 2018; Nasello et al, 2020; Thrivikraman et al, 2019), which significantly improved the physiological relevance of bone cell cultures compared to previously used monolayer systems. These studies showed that mechanical stimulation (Akiva et al, 2021; Budyn et al, 2018) and matrix stiffness (Thrivikraman et al, 2019) are critical influencers of bone formation with regard to differentiation and bone matrix maturation. Remarkably, some of these 3D models showed that inducing longitudinal strain by fixation of a 3D cell culture on opposite sides was enough to induce matrix alignment and aligned mineralization (Iordachescu et al, 2018; Sasaki et al, 2010; Sasaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%